Cabello Port, January 3, 1827 (2010)
My dear general: From Maracaibo I have not written to you because I was on the march to this square, where I now arrived three days. I found it in open war with Valencia; I had news of the state from the West and East of Venezuela, where it was already fighting, and lately General Silva came to give me news of the Llano, which was already burning.